KIAA1797/FOCAD encodes a novel focal adhesion protein with tumour suppressor function in gliomas - Brockschmidt, Antje; Peterziel, Heike; Wick, Wolfgang; Angel, Peter (Brain, 2012)
Abstract. In a strategy to identify novel genes involved in glioma pathogenesis by molecular characterization of chromosomal translocation breakpoints, we iden